(untitled) (Third Sector Social Economic Review, 2021)
Hospitals present their corporate information to stakeholder groups through their websites. These communication tools must be used effectively. The study aims to examine the websites of public and private hospitals in Ankara in terms of communication with society. Within the scope of the research, a total of 77 websites were examined in terms of 51 criteria under 6 sections using the content analysis method, which is one of the qualitative research methods. The data were analyzed using IBM SPSS Statistics Ver. 20 (IBM SPSS Statistics for Windows Version 20 Armonk, NY:IBM Corp). Findings of the study show that while hospitals have some features on their websites, they don’t give importance to others. Private hospitals in Ankara don’t provide sufficient information about hospital history and visual images on their websites, and don’t provide announcements and frequently asked questions. On the other hand, public hospitals don’t provide adequate information about hospital slogans and physician CVs on their websites, and both public and private hospitals don’t have efficient language options in a city with a high potential for international patients.